Effects of vitamin C on cardiovascular oxidative stress induced by hypothyroidism in neonatal and juvenile rats - Farimah Beheshti; Reza Mohebbati; Mahmoud Hosseini; Saeed Niazmand; Masomeh Mirzaei; Mahdiyeh Hedayati-Moghadam; Maryam Paseban (Future Natural Products)
Background and aims: Hypothyroidism and cardiovascular diseases are associated with oxidative stress. Vitamin C is widely recognized for its antioxidant properties. This study aimed to investigate the effects of vitamin C during the neonatal and juvenile periods on oxidative stress induced by hypothyroidism in the hearts of rats. Methods: Sixteen pregnant rats were randomly divided into five groups after delivery: a control group, a group receiving propylthiouracil (PTU), and three treatment groups receiving PTU along with 10, 100, and 500 mg/kg of vitamin C. The experimental treatments continued for the first eight weeks of the offspring’s life, following the lactation period, and the offspring were treated in the same manner. At the end of the study, the rats were sacrificed, and serum, aortic, and cardiac tissues were collected for antioxidant evaluation. Results: In the group receiving PTU, levels of thyroxine and antioxidant enzymes were decreased in serum, heart, and aortic tissues. In contrast, the groups receiving PTU along with various doses of vitamin C demonstrated an attenuation of these parameters. Conclusion: Based on the findings, vitamin C supplementation improved cardiovascular oxidative stress induced by hypothyroidism in rats.